(العلّامة خواهرزاد- ت1935م) وآراؤه الكلامية في النبوات والسمعيات من خلال تفسيره(تيزكاری ئيمان بۆ قەومی كوردان- تذكار الإيمان للشعب الكردي) دراسة تحليلية - بابكر, أ.د. محمد أحمد; حمه, هادي محمدلطيف (Sulaimani Journal for Humanities, 2023)
Xwahrzad is Mohammed Ibn Abdul Karem. He was born in Pinjwen City in Kurdistan, He retired from secular matters and took on studying and writing till he died in (1335 H). He left behind a great legacy of books in all fields of sciences such as religion, philosophy, logics. One of his most famous books is his Quran Interpretation entitled, " Tizkary Eman bo kawmi Kurdan " His ideas were approved by Alashaera in most philosophical issues such as knowing the entity of God unlike Almotazellah doctrine that is based on using mind to reach the entity of God. Faith Xwahrzad is just believing by heart. This is the same belief of Alashaerah and Morjea and others. Also, he believes that God's words are as old as God Himself without hearing seeing Him except for the sight of God in the Day of Judgment by the believers who will be able to see Him without thinking over the way of doing that. In the part of (the fate) or destiny. His believes and doctrines were approved by the Sunnah Sect except for the issues concerned with fate such as negating purposes in the deeds of God and other similar issues dealt with in this research. However, His proving to the Monotheism of God, prophecy and the Day of Resurrection were approved by the Doctrine of the Sunnah Sect. These are his believes deduced from his interpretation. I beg my Lord to accept this work and dedicate it to Him only and peace be upon his apostle, Mohammed Peace be upon him.
Keywords: خوهرزاد تذكار النبوات السمعيات